Seimbangkan Kuliah dan Kerja: Panduan Praktis Hadapi Tantangan dan Raih Cita-Cita - Lidya Pricilla; Lili Indriyani; Sri Kurnia Wati Gulo; Sukma Nur Adzan (Jurnal PKM Manajemen Bisnis, 2026)
Balancing study and work has become a growing challenge for students in today’s fast-paced educational and professional environments. Many students struggle to manage their time, maintain academic performance, and achieve personal goals while working part-time. This community service program (PKM) titled “Balancing Study and Work: A Practical Guide to Overcome Challenges and Achieve Dreams” was designed to provide practical strategies for managing both academic and work responsibilities effectively. The activity took place at SMK Perguruan Rakyat 1 Jakarta on October 31, 2025, involving 16 lecturers and students from Universitas Pamulang as facilitators, and 50 vocational high school students as participants. The PKM was implemented through several stages: preparation, implementation, and reporting. The implementation phase included material presentations, group discussions, and question-and-answer sessions to actively engage participants. The results of the activity showed that students gained better understanding of time management, motivation building, and goal-setting strategies, which are essential for maintaining balance between study and work. Participants expressed increased awareness and confidence in planning their future academic and career paths. Overall, the program successfully enhanced students’ knowledge and readiness to face the dual role of worker and student in pursuing their aspirations.